Penerapan media pembelajaran match up untuk meningkatkan semangat belajar siswa pada mata pelajaran kajian keislaman materi Dzikir dan Doa - Nugraha, Aqilah Fadiah (Maliki Interdisciplinary Journal, 2024)
This research aims to examine the application of Match Up learning media in increasing students’ enthusiasm for learning on Dhikr and Prayer material. The process of developing learning media involves several critical stages, starting from needs analysis, design, development, implementation, to work evaluation. The first stage, needs analysis, was carried out through surveys and interviews with teachers and students to identify problems in learning Dhikr and Prayer and determine the specific media needs required. The second stage, design, includes creating learning scenarios and initial design of interactive and interesting Match Up media. The third stage, development, involves creating complete learning media and initial testing on a number of students to obtain input and make revisions. The fourth stage, implementation, Match Up media is applied in the classroom learning process by involving all students. The final stage, work evaluation, is carried out to assess the effectiveness of the media through observations, questionnaires and tests on student learning outcomes. The research results show that the use of Match Up learning media significantly increases students’ enthusiasm and active participation in studying Dhikr and Prayer material. Evaluation also shows an increase in student learning outcomes after implementing this media. In conclusion, Match Up learning media is effective in increasing students’ enthusiasm for learning and can be used as an innovative alternative in religious learning at school.